2018
DOI: 10.1029/2018gl077560
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Shadow: The Shifting Role of Shaded Leaves in Global Carbon and Water Cycles Under Climate Change

Abstract: Globally shaded leaves contribute to more than a half of the total increase in gross primary production (GPP; 7.6 Pg C) for 1982–2016. During 1982–2016, the fraction of shaded GPP increases by 1.1% (p < 0.01) in tropical forests and decreases by 1.4% (p < 0.01) and 1.8% (p < 0.01) in evergreen needleleaf and deciduous needleleaf boreal forests, respectively, suggesting an ecological niche of certain canopy structure for ecosystems to achieve maximum GPP. Unlike transpiration from sunlit leaves that has a turni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 105 publications
(140 reference statements)
1
43
0
Order By: Relevance
“…The Boreal Ecosystems Productivity Simulator (BEPS), hourly version, is a process-based ecosystem model to simulate water, energy, and carbon budgets [47][48][49][50][51][52]; it was used in this study to simulate cotton GPP. BEPS is in development for the last years [53].…”
Section: Ecosystem Model For Gpp Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The Boreal Ecosystems Productivity Simulator (BEPS), hourly version, is a process-based ecosystem model to simulate water, energy, and carbon budgets [47][48][49][50][51][52]; it was used in this study to simulate cotton GPP. BEPS is in development for the last years [53].…”
Section: Ecosystem Model For Gpp Simulationmentioning
confidence: 99%
“…BEPS is in development for the last years [53]. Although BEPS was initially developed for boreal ecosystems, it was expanded and used for temperate and tropical ecosystems in regional and global scales [48,51,52,[54][55][56][57][58][59] and for the estimation of winter wheat yield in China [18], as C3 plants share the same photosynthesis theory at the leaf level, i.e., Farquhar's leaf-level biochemical model [60], and BEPS has a "two-leaf" approach to upscale the ecosystem GPP to canopy level for various ecosystems including crops [49,61].…”
Section: Ecosystem Model For Gpp Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The four component proportions directly determine the forest canopy spectral characteristics [9] and further affect the retrieval accuracy of forest leaf area index (LAI) [10,11] and chlorophyll content [12]. Then characterizing the sunlit and shaded components in a forest stand will be beneficial to the calculation of C assimilation and transpiration using advanced ecosystem models [13].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that understory vegetation contributes 32% of the total GPP in tropical forests [22,23], but this contribution may be 25% in temperate forests [24]. A recent study showed that the shaded GPP has increased by 1.1% over the past three decades [25]. This variability is due to variations in the light, temperature, and humidity conditions in the understory and overstory.…”
Section: Introductionmentioning
confidence: 99%